2009
DOI: 10.1099/vir.0.010058-0
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in human neural cells following tick-borne encephalitis virus infection

Abstract: Tick-borne encephalitis (TBE) is one of the leading and most dangerous human viral neuroinfections in Europe and north-eastern Asia. The clinical manifestations include asymptomatic infections, fevers and debilitating encephalitis that might progress into chronic disease or fatal infection. To understand TBE pathology further in host nervous systems, three human neural cell lines, neuroblastoma, medulloblastoma and glioblastoma, were infected with TBE virus (TBEV). The susceptibility and virus-mediated cytopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
54
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 51 publications
6
54
0
Order By: Relevance
“…In a previous study, we compared TBEV growth in human neuroblastoma, glioblastoma, medulloblastoma, and PS cells. That study showed that virus replication in neural cell lines was more than 100 times more efficient than in the PS cells14. In the present study, we showed that primary HNs were also highly sensitive to TBEV infection, and they also produced high virus titers.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In a previous study, we compared TBEV growth in human neuroblastoma, glioblastoma, medulloblastoma, and PS cells. That study showed that virus replication in neural cell lines was more than 100 times more efficient than in the PS cells14. In the present study, we showed that primary HNs were also highly sensitive to TBEV infection, and they also produced high virus titers.…”
Section: Discussionsupporting
confidence: 58%
“…Various cellular models, including neuronal cell lines, primary cultures of embryonic or neonatal mouse and rat neuronal cells, and neurons derived from embryonic stem cells, have been used to explore infections with various neurotropic viruses (e.g., polio, herpes simplex type 1, varicella-zoster, West Nile, Japanese encephalitis, and rabies)10111213. We previously examined TBEV infections in human neural (neuroblastoma, glioblastoma, and medulloblastoma) cell lines14. On the ultrastructural level, the infection caused massive morphological changes in cells, including the proliferation and rearrangement of rough endoplasmic reticulum (RER) and signs of apoptosis or necrosis14.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PS cells are widely used for TBEV isolation and for multiplication and plaque assays (30). Human neuroblastoma cells are highly sensitive to TBEV infection and represent a valuable model for neuropathogenesis studies of TBEV as well as for studies of several other neurotropic viruses (31). The initial screening was performed using two TBEV strains, Neudoerfl and Hypr, which represent two virulence models.…”
Section: Discussionmentioning
confidence: 99%
“…Porcine kidney stable (PS) cells were cultured at 37°C in Leibovitz (L-15) medium supplemented with 3% precolostral calf serum and a 1% mixture of penicillin and glutamine (Sigma-Aldrich, Prague, Czech Republic) (30). Human neuroblastoma UKF-NB-4 cells were cultured at 37°C in 5% CO 2 in Iscove's modified Dulbecco's medium (IMDM) supplemented with 10% fetal bovine serum and a 1% mixture of penicillin and streptomycin (Sigma-Aldrich) (31). All experiments were performed with TBEV strains Hypr and Neudoerfl, which are representatives of the West European TBEV subtype.…”
Section: Methodsmentioning
confidence: 99%